ANALISIS PENGARUH KREATIVITAS DISPLAY, DAN PROMOSI STORE AID TERHADAP CUSTOMER DELIGHT DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN Studi pada Aneka Jaya Perum Sambiroto Semarang - Dora, sylvia Terra; Sugiarto, Sugiarto; Mudiantono, Mudiantono (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
The purpose of this research is to test the influences of display creativity and store promotional aid on customer delight to improve purchasing decisions. Using these variables, the usage of these variables are able to solve the arising problem in the branch of Aneka Jaya departement store Semarang city.The samples size of this research is 114 buyer of Aneka Jaya Departement store Semarang. Using the Structural Equation Modelling (SEM), the result shows that the display creativity and store promotional aid have influence on customer delight in order to improve purchasing decisions.The effect of display creativity on customer delight are significant; the effect of store promotional aid on customer delight are significant; The effect of display creativity on purchasing decisions are significant; the effect of store promotional aid on purchasing decisions are significant; and the effect of customer delight on purhasing decisions are significant.